PERBANDINGAN KEMAMPUAN MEMECAHKAN MASALAH STRUKTUR ALJABAR ANTARA MAHASISWA JARAK JAUH DAN MAHASISWA TATAP MUKA - Endang Wahyuningrum (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2007)
Learning to solve problems is the principal reason for studying mathematics. Teachers play important roles to enhance students’ ability to solve problems in mathematics. While teachers’ presence is common situation in face-to-face education system, it’s hardly the case in distance education system. The situation often post questions on the quality of distance education system, especially in the field of mathematics. The aim of this research was to compare students’ form distance education system and face-to-face system in term of the students’ achievement in problem solving. Data collected through questionnaires and written test are analyzed quantitatively to compare the algebra structure problem solving competences between the groups of students based on Polya's phase guide for solving problem. Analysis shows that the average scores of face-to-face students are slightly higher than distance education students. However, on one out of four competences -how to prove the subgroup- there is no differences in the two groups average scores